Representation and Embassy Protection - Janicek, Miroslav (Communications - Scientific letters of the University of Zilina, 2008)
In this article, on the basis of his theoretical and practical experience, the author tried to outline briefly the main principles and rules of protection of important objects nowadays, when there is higher hazard of possible terrorist attack. His conclusions may significantly stand interested people in these problems from both professional and laical public in good stead, as abasis or „point of bounce“. It can help significantly to specialists from this field.